Formononetin Attenuates Airway Inﬂammation and Oxidative Stress in Murine Allergic Asthma - La Yi (Frontiers in Pharmacology, 2020)
Allergic asthma has been considered as a respiratory disorder with pathological features of airway inflammation and remodeling, which involves oxidative stress. Formononetin (FMT) is a bioactive isoflavone obtained from Chinese herb Radix Astragali, and has been reported to have notable anti-inflammatory and antioxidant effects in several diseases. The purpose of our study was to elaborate the effects of FMT on asthma and the underlying mechanisms. To establish allergic asthma model, BALB/c mice were given ovalbumin (OVA) sensitization and challenge, treated with FMT (10, 20, 40 mg/kg) or dexamethasone (2 mg/kg). The effects of FMT on lung inflammation and oxidative stress were assessed. In OVA-induced asthmatic mice, FMT treatments significantly ameliorated lung function, alleviated lung inflammation including infiltration of inflammatory cells, the elevated levels of interleukin (IL)-4, IL-5, and IL-13, immunoglobulin (Ig) E, C-C motif chemokine ligand 5 (CCL5, also known as RANTES), CCL11 (also called Eotaxin-1), and IL-17A. In addition, FMT treatments eminently blunted goblet cell hyperplasia and collagen deposition, and remarkably reduced oxidative stress as displayed by decreased reactive oxygen species (ROS), and increased superoxide diamutase (SOD) activity. Furthermore, to clarify the potential mechanisms responsible for the effects, we determined the inflammation and oxidation-related signaling pathway including nuclear factor kappa β (NF-κB), c-Jun N-terminal kinase (JNK), and the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). FMT treatments appeared to dramatically inhibit the activation of NF-κB and JNK, significantly elevated the expression of heme oxygenase 1 (HO-1) but failed to activate expression of Nrf2. In conclusion, our study suggested that FMT had the therapeutic effects in attenuating airway inflammation and oxidative stress in asthma.